Folic acid ameliorates alcohol-induced liver injury via gut–liver axis homeostasis - Zhang, Huaqi; Zuo, Yuwei; Zhao, Huichao; Zhao, Hui; Wang, Yutong; Zhang, Xinyu; Zhang, Jiacheng; Wang, Peng; Sun, Lirui; Zhang, Huizhen; Liang, Hui (Frontiers in Nutrition, 2022)
Gut-liver axis (GLA) plays an important role in the development of alcohol-induced liver injury. Alcohol consumption is typically accompanied with folic acid deficiency. However, no clear evidence has confirmed the effect of folic acid supplementation on alcohol-induced liver injury via GLA homeostasis. In this study, male C57BL/6J mice were given 56%(v/v) ethanol and 5.0 mg/kg folic acid by gavage for ten weeks to investigate potential protective mechanisms of folic acid for alcohol-induced liver injury via GLA homeostasis. Histopathological and biochemical analysis showed that folic acid improved lipid deposition and inflammation in liver by alcohol, and decreased the level of ALT, AST, TG and LPS in serum. Folic acid inhibited the expression of TLR4 signaling pathway and its downstream inflammatory mediators in liver, and up-regulated the expression of ZO-1, Claudin 1 and Occludin in intestine. But compared with CON group, folic acid did not completely eliminate alcohol induced intestine and liver injury. Furthermore, folic acid regulated alcohol-induced alterations in gut microbiota. Folic acid significantly increased the relative abundance of Verrucomicrobia, Actinobacteria, Akkermansia and Bifidobacterium, and decreased the relative abundance of Bacteriodetes and Rikenellaceae_RC9_gut_group. Folic acid significantly increased the phenotype abundance of Forms_Biofilms and decreased the phenotype abundance of Potentially_Pathogenic and Stress_Tolerant. The results of spearman’s correlation analysis showed that serum parameters and hepatic inflammatory cytokines were significantly correlated with several bacteria, mainly including Bacteroidetes, Firmicutes and uncultured_bacterium_f_Lachnospiraceae. In conclusion, folic acid could ameliorate alcohol-induced liver injury in mice via GLA homeostasis to some extent, providing a new idea and method for prevention of alcohol-induced liver injury.